Conformational study of (E)-4-{1-[2-(carbamothioyl) hydrazin phenyl-4-methylbenzoate (C17H17N3O2S - HONFODJI, Wilfried; Kanhounnon, G. Wilfried; KUEVI, HORTENSIA VICENTIA; ATOHOUN, YACOLÈ GUY SYLVAIN (My University, 2018)
The (E)-4-{1-[2-(carbamothioyl) hydrazine formula. As several thiosemicarbazones, it has some pharmacological properties. By HF and DFT/B3LYP methods as implemented in the gaussian 09, in the 6-31G, 6 molecule was performed. Among the molecule conformers modelled, the calculated values of geometrical parameters of two are very close to crystallographic data. Besides, the trypanocide predicting model established by DFT/B3LYP/6
Keywords: Hartree Fock (HF); density functional theory (DFT); thiosemicarbazone; conformers; trypanocide.